An overview of CO2 conversion in a microwave discharge: the role of plasma-catalysis. (25th January 2017) - Chen, Guoxing; Britun, Nikolay; Godfroid, Thomas; Georgieva, Violeta; Snyders, Rony; Delplancke-Ogletree, Marie-Paule
Abstract: An overview of the recent progress on plasma-assisted CO2 conversion in microwave discharges is given. Special attention is devoted to the results obtained using plasma catalysis, which are compared to the plasma-only CO2 decomposition cases. The effects of plasma operating conditions, catalyst preparation methods, nature of plasma activation gas, gas mixture, as well as the NiO content on the TiO2 surface on CO2 conversion and its energy efficiency are discussed. A significant improvement in CO2 conversion is obtained with a NiO/TiO2 catalyst activated in Ar plasma, when the NiO content is about 10 wt.%. The catalyst characterization data show that Ar plasma treatment results in a higher density of oxygen vacancies and a comparatively more uniform distribution of NiO on the TiO2 surface, which strongly influence CO2 conversion and its energy efficiency. The dissociative electron attachment of CO2 at the catalyst surface enhanced by the oxygen vacancies and by plasma electrons may also explain the increase in conversion and energy efficiencies. A mechanism for the plasma-catalytic CO2 conversion at the surface of an Ar plasma-threated catalyst is proposed.